SOSIALISASI PROLANIS PADA POSBINDU MANGGULAN RT 06 RW 07 SANGGRAHAN DALAM RANGKA MENCEGAH TERJADINYA PENUMPUKAN RUJUKAN PENYAKIT KRONIS PADA RUMAH SAKIT (FKTL) - Ahmad Yani Noor (Permata Indonesia, 2023)
Chronic disease is a disease that is the main cause of death in Indonesia. The incidence of chronicdiseases in Indonesia has increased based on the results of the 2018 Basic Health Research comparedto the results of the 2013 Basic Health Research. Since 2014, the implementation of the Chronic DiseaseControl Program (hereinafter referred to as Prolanis) from the government has not gone well in severalregions. The obstacles that occur are the lack of cooperation from all parties and the community's noncompliance with Prolanis. Currently, movements, communities and community groups have emergedwith positive activities, one of which is the Manggulan Posbindu (Integrated Post) located in SanggrahanHamlet, Sleman Regency. Posbindu Mangulan in collaboration with the Yogyakarta Permata IndonesiaHealth Polytechnic created a series of activities to make Prolanis a success, including free blood sugarand blood pressure checks, as well as outreach and discussion about Prolanis. This activity is attendedby 20 participants and will be held regularly. It is hoped that the high enthusiasm of the participants inthe discussion process and a series of examination activities will make Prolanis successful and preventthe accumulation of chronic disease referrals at the hospital.